Genetic and environmental influences on beef cattle production in Zambia. 4. Weaner production from purebred and reciprocally crossbred dams - Thorpe, W.R.; Cruickshank, D.K.R.; Thompson, R. (Cambridge University Press, 1981)
Dam reproductive performance of purebred Africander, Angoni, Barotse and Boran, and reciprocal crossbreds of the latter 3 breeds under ranching conditions were investigated. Mean performance based on a maximum of 1996 records collected over six parities were: calving rate, 65.6%; weaning weight rate, 62.8%; calf birth weight, 26.6 kg; calf weaning weight, 163.6 kg; and dam live weight at weaning 363.0 kg. Comparative evaluations of dam performance indicated that there were no differences between reciprocal crossbred dams for calving and weaning percentages; dam status at mating had an important effect on fertility; there were large differences between breeds for calf weights but heterosis estimates were small and non-significant; there were no differences between progeny weights of reciprocal crossbred dams; dams which lost most live weight during the breeding season had significantly poorer fertility. Sex, date and period of birth, and dam status had significant effects on calf weight. Overall estimates of heritability derived by dam/daughter regression were 0.20 for calving percentage, 0.76 for calf birth weight and 0.72 for weaning weight.